Impact of patient's health-related quality of life on physicians' therapy and perceived benefit in acute coronary syndromes: protocol for a systemic review of quantitative and qualitative studies. Issue 2 (27th February 2019) - Kaambwa, Billingsley; Gesesew, Hailay; Horsfall, Matthew; Chew, Derek P
Abstract : Introduction: Percutaneous coronary interventions (PCIs) and coronary angiography are two of the treatments administered to acute coronary syndrome (ACS) patients. However, whether and how patients' health-related quality of life (HRQoL) influences treatment decisions and subsequent risk benefit analyses is unclear. In this study, we will review the available evidence on the impact of patients' HRQoL on physicians' prescribing or treatment decisions and on the estimation of mortality and bleeding risk in ACS patients. Methods and analysis: We will undertake a systematic review of all quantitative and qualitative studies. The search will include studies that describe the impact of HRQoL on prescribing PCIs or angiography, and impact of HRQoL on perceived risks in terms of mortality and bleeding events. We will conduct an initial search on Google scholar and MEDLINE to build the searching terms followed by a full search strategy using all identified keywords and index terms across the five databases, namely MEDLINE, PubMed, CINAHL, SCOPUS and Web of Sciences. We will use the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for protocol guidelines to present the protocol. Only English language articles will be included for the review. We will use a standardised Joanna Briggs Institute data extraction tool to synthesise the information extracted from the selected studies into themes with summary findings presented in a table. Ethics and dissemination: We will not require a formal ethical approval as we will not be collecting primary data. Review findings will be disseminated through a peer-reviewed publication, workshops, conference presentations and a media release. PROSPERO registration number: CRD42018108438.